Management Of The Educational Process Through Development Of Creative School Educational Organization Teachers - Dilmira Farhodovna Salimova (Euro Asian Journal Publishing, 2024)
The article discusses that teachers of a preschool educational organization must have solid knowledge and skills, the formation of their creative abilities, and also manage educational activitiesin development centers through various games with a creative approach.
Keywords: preschool age; role-playing game; creativity; teacher-teacher